Volatile Alteration and Metamorphic Facies: Release of H2O and CO2 in the Panjal Volcanics of the NW Himalaya - Spencer, David A. (Journal of Nepal Geological Society, 1995)
Whilst the bulk rock geochemistry of a basalt, subjected to progressively increasing metamorphic grade, may remain on the whole isochemical, it has been long known that volatiles are likely to be released. Three volatiles which should change through an increase in metamorphic grade are H2O, CO2 and O2. The various metamorphic grades of the Panjal Volcanics in the NW Himalayas (unmetamorphosed, greenschist, amphibolite and eclogite facies) provide an ideal opportunity to test these ideas and possibly act as chemical indicators of the prograde metamorphism. Direct and indirect determination of CO2 and H2O were made on numerous samples. Direct determination of CO2 content in a rock sample has been made by coulometric titration for five main groups: Zanskar Tethyan Shelf - Panjal Volcanic basalts (Ba); Lesser Himalaya- Panjal Volcanic basalts (PJ); Higher Himalaya Second Cover - Panjal Volcanic amphibolites (A); Higher Himalaya Second Cover - Panjal Volcanic dolerites (D) and Higher Himalaya Second Cover - Panjal Volcanic eclogites (E). The main observation on the occurrence of % CO2 in the Panjal Volcanics with increasing metamorphic grade is that there is a decrease in CO2 that appears to be fairly gradual. This therefore suggests that with increasing metamorphism, CO2 is being driven off by decarbonation reactions. Estimation of the volatile content in a sample can be made by the simple2weight loss on ignition, and used as a method of indirect determination of H2O. The loss on ignition (L.O.I.) and the H2O (+ FeO) in the Panjal Volcanics show that with an increase in metamorphic grade there is a decrease in the L.O.I. and H2O (+ FeO) content. This therefore suggests that with increasing metamorphism, volatiles are being removed by dehydration reactions. Comparison of the results of this work with the results of some published theoretical calculations are made for the wt. % H2O of a subducting, and therefore dehydrating, oceanic crust or tholeiitic basalt. Here, predictions were made by combining calculated pressure - temperature paths with a model of metabasalt phase equilibria, where a progression (for the upper parts of the oceanic crust) pass through greenschist to amphibolite to eclogite facies. The agreement between these two independently produced sets of data is clearly apparent.